Overview of the liquid natural gas (LNG) regasification technologies with the special focus on the Prof. Szargut's impact. (15th December 2018) - Szczygiel, Ireneusz; Bulinski, Zbigniew
Abstract: In the paper the overview of available technologies for Liquefied Natural Gas regasification is presented. Special emphasis is put on the Prof. Szargut's input to the topic. Both existing and theoretical solutions are shown. Additionally, the zero-order mathematical of on og the technologies is presented.